Effect of Date Palm Thinning Applications on Chemical Properties of Barhi Cultivar in Ripening Stage - M. A. Hamed, Manar; Abdelkader A.M. Sallam, Saeed A. Mehana and (Journal of Neonatal Surgery, 2024)
This investigation was carried out during the two consecutive seasons, 2023 and 2024 respectively on date palm trees (Phoenix dactylifera L.) cv. Barhi grown in a private orchard at Belbis region, Sharkia Governorate, Egypt to evaluate the impact of thinning applications by bunches number and thinning levels using exclusive tools on the yield and fruit quality. Fortyfive date palm trees (fifteen treatments with three replicates for each treatment) were selected in both studied seasons. In a sandy soil and irrigated with drip irrigation system. Date Palm trees were 10-year-old, planted at 8*8m space. Chemical content of Carotenoids of Barhi date palm was affected markedly by thinning methods during the two seasons researches at ripening stage, which raised the dry matter and moisture especially when used 8 bunches/palm in the two seasons. Interaction between bunches number and thinning methods of pincers treatment in 10 bunches/ palm gave the highest value 53.6% in the second season as compared to control palm gave the minimum values 34.5 and 35.3 % in both seasons respectively. Also bunches number on dry matter showed maximum values (59.5 and 58.4 %) by used 8 bunches / palm in the two seasons respectively. Carotenoids content was affected by bunches number at ripening stage markedly in the first season only. Moreover, thinning methods of comb showed maximum values (8.38 and 9.30 mg) in the both seasons, while the control palm showed the lowest results (4.63 and 5.17mg) in both seasons,respectively.Total chlorophyll at ripening stage of Barhi date palm revealed that maximum values were affected by bunches number in 10 bunches/ palm in both seasons. While 10 bunches/palm gave the lowest results (2.8 and 2.7 mg) in both seasons. Total tannins at ripening stage of Barhi date palm wasaffected by bunches number,whichgave the minimum values by 12 bunches/palm in the two seasons ,while the maximum results showed in 8 bunches/palm in the two seasons, respectively. Also thinning methods showed the lowest content of total tannins with central strands in the first season, however the highest content showed by control palm in the two seasons respectively. Pincers thinning methods gave the greatest results of TSS (34.0) in the first season also comb thinning gave the same trend of TSS in the second season. The acidity at ripening stage of Barhi date palm gave the lowest values by 8 bunches/palm in the two seasons of study. Pincers thinning method showed the least values of total acidity at ripening stage during the two studied seasons. The interaction between bunches number and thinning methods revealed the lowest by pincers+10 bunches/palm during both seasons. While control palm+12 bunches/palm treatment showed vice versa in this concern. TSS/Acid ratio of Barhi date palm at ripening stage showed a maximum valuesby pincers thinning method during the two seasons, while the lowest values revealed by control palm in both seasons. Vitamin C content of Barhi date palm at ripening stage showed the highest values (3.68 and 3.80 mg) when used 10 bunches/ palm in both seasons. While the least values (3.20 and 3.54 mg) revealed by 12 bunches/palm during two seasons. Howeverpincers thinning methods gave the greatest values (3.70 and 4.05 mg) in both seasons, respectively. The control palm had vice versa in this respect. Bunches number was affected on reducing sugars at ripening stage of Barhi date palm, which gave the maximum values (44.4 and 43.6 %) by used 8 bunches/ palm in the two seasons. Thinning methods affected on reducing sugars especially pincers treatment gave the highest value (41.3%) during the first season. Additionally control palm showed the lowest values (33.6 and 33.0 %) during the two seasons, respectively. Non-reducing sugars was affected by bunches number markedly in the first season only. Howeverthinning methods especially pincers thinning method showed the greatest values (4.84 and 4.98 %) in the two seasons. Total sugars content % at ripening stage was affected by bunches number / palm which eight bunches/palm showed the highest values (48.3 and 47.2 %) in both seasons. Also thinning methods affected on total sugars by pincers treatment during the two seasons, respectively. Conclusively: from this resultsof research, improving of fruits chemical properties by thinning methods especially pincers and comb tools in Barhi date palm.